A Consensus-Based Current Sharing Algorithm for Energy Storage Systems: An Application to Aeronautic Microgrids - Giacomo Canciello; Antonio Russo; Alberto Cavallo (IEEE Access)
More Electric Aircraft (MEA) and All Electric Aircraft (AEA) require advanced autonomous electric Energy Management Systems (EMS) onboard the aircraft. The aircraft electric network can be considered as an islanded microgrid, and as such some approaches typical of the microgrid management can be used onboard the aircraft to design an effective EMS. In particular, distributed control with consensus techniques represents a promising approach due to the advantages in terms of reliability, computational simplicity and low-bandwidth requirement which are of great interest for implementation onboard. A consensus-based solution to the problem of coordinating and balancing several Energy Storage Systems (ESSs) coexisting in a generic aircraft architecture is proposed and analyzed. The proposed algorithm selects the current setpoints for each ESS according to their state of charge while ensuring safety of operations. Theoretical results and detailed simulations show the effectiveness of the proposed approach.